# Find the Union (or) z+y>6 , z-y=4 z+y>6 , z-y=4
Subtract z from both sides of the inequality.
y>6-z or z-y=4
Simplify the second inequality.
Subtract z from both sides of the equation.
y>6-z or -y=4-z
Multiply each term in -y=4-z by -1
Multiply each term in -y=4-z by -1.
y>6-z or (-y)⋅-1=4⋅-1+(-z)⋅-1
Multiply (-y)⋅-1.
Multiply -1 by -1.
y>6-z or 1y=4⋅-1+(-z)⋅-1
Multiply y by 1.
y>6-z or y=4⋅-1+(-z)⋅-1
y>6-z or y=4⋅-1+(-z)⋅-1
Simplify each term.
Multiply 4 by -1.
y>6-z or y=-4+(-z)⋅-1
Multiply (-z)⋅-1.
Multiply -1 by -1.
y>6-z or y=-4+1z
Multiply z by 1.
y>6-z or y=-4+z
y>6-z or y=-4+z
y>6-z or y=-4+z
y>6-z or y=-4+z
y>6-z or y=-4+z
6-z","isGrey":false,"dashed":false,"holes":[]},{"ascii":"y=-4+z","isGrey":false,"dashed":false,"holes":[]}],"asymptotes":[],"segments":[],"areaBetweenCurves":[],"points":[],"HasGraphInput":true}” class=”GraphWrapper”>
Find the Union (or) z+y>6 , z-y=4

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top